2017
DOI: 10.1007/s00213-017-4676-8
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and reversal of social stress-escalated cocaine self-administration in mice by intra-VTA CRFR1 antagonism

Abstract: Background A history of brief intermittent social defeat stress can escalate cocaine self-administration and induce long-term adaptations in the mesolimbic dopamine system. Extra-hypothalamic corticotrophin releasing factor (CRF) has been shown to be closely associated with stress-induced escalation of drug use. How repeated stress modulates CRF release in the ventral tegmental area (VTA) and the roles of CRF receptors during different phases of stress-induced cocaine self-administration remain to be defined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…; Hansson et al . ; Han, DeBold, & Miczek ; Leonard, DeBold, & Miczek ). A remaining open question is whether msP and Wistar rats differ also in their propensity to relapse in response to environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…; Hansson et al . ; Han, DeBold, & Miczek ; Leonard, DeBold, & Miczek ). A remaining open question is whether msP and Wistar rats differ also in their propensity to relapse in response to environmental cues.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of SD on cocaine SA have been extensively studied in adult rats (Miczek et al., ). Miczek's laboratory has persistently reported that SD increases both acquisition of cocaine SA and motivation to take the drug, raising the breaking point in the progressive ratio program (Boyson et al., ; Covington et al., ; Han et al., ; Quadros & Miczek, ). Studies use short‐term access to the drug, resulting in very controlled and stable levels of drug SA.…”
Section: Effects Of Social Defeat On Psychostimulant and Alcohol Rewardmentioning
confidence: 99%
“…Social stress promotes the release of CRF in the VTA when there is both acute and repeated social stress (Holly et al., ). Recently, researchers have related this increase in basal levels of CRF in the VTA with the escalation on cocaine SA and the development of behavioral and neural cross‐sensitization that takes place in defeated animals (Boyson et al., ; Han et al., ; Holly et al., ). These CRF effects are mediated by two receptors, namely CRF receptor type 1 (CRFR1) and CRF receptor type 2 (CRFR2), both positively coupled to adenylate cyclase through stimulatory G proteins (Binder & Nemeroff, ; Hauger, Risbrough, Oakley, Olivares‐Reyes, & Dautzenberg, ; Zorrilla & Koob, ).…”
Section: Mechanisms Underlying the Effects Of Social Defeat Stress Onmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute stress influences a host of behaviors through the actions of CRF in the VTA, with effects on motivation, decision-making, subsequent drug intake, and drug seeking [3,4,6,7,[20][21][22]. Intriguingly, midbrain CRF suppresses dopamine-dependent behaviors in drugnaïve animals [3,4], whereas CRF promotes dopamine-dependent behaviors in drug-experienced animals [6,7,[20][21][22]. These conflicting reports indicate that the behavioral effects of CRF in the midbrain are either reinforcer-specific, or alternatively depend upon prior drug experience.…”
Section: Discussionmentioning
confidence: 99%